Efficacy of formulated anti-mosquito gel from eucalyptus (Eucalyptus globules) and carrageenan - Alcon, Charie Mayne; Blanco, Ma. Tereza A.; Agrupis, Shirley C. (2011)
The in vitro and in situ biocidal property of Eucalyptus gel formulation against larval mosquitoes was evaluated. The study aimed to (1) determine the effects on the morphology of mosquitoes: and (2) determine the mosquito repellent effect of the gel formulation. Eight (8) different treatments were prepared for the in vitro test namely: T1 (combination of carrageenan and eucalyptus oil; T2 (combination of carrageenan and eucalyptus powder; T3 (pure carrageenan); T4 (pure eucalyptus oil); T5 (pure eucalyptus powder); T6 and T7 (positive control, commercial anti mosquito lotion for kids and adult); and T8 (negative control). Morphological effects of formulated treatments on the larval mosquitoes include the loss of body fluid, antennae and cut hair-like structures. In terms of mortality rate, eucalyptus oil formulation was not significantly different from the positive control, which both achieved 100% mortality. Based on the in vitro test, pure eucalyptus oil was observed as the most effective in attaining 100% mortality in just 29.33 minutes after application. The first three (3) formulations that gave the best result were used in the in situ evaluation namely T1, T2 and T4. The in situ evaluation revealed that the combination of carrageenan and eucalyptus oil (T1) and commercial anti-mosquito lotion gave the best result in which no mosquito bites were observed by the human samples. Coefficient of Variation (CV) revealed that there are no significant differences between the formulated treatments and positive control on the number of mosquito bites. The abundance of eucalyptus plant in the country can be tapped for the production of environment-friendly anti-mosquito product.
Keywords: Eucalyptus; Mosquito control; Insecticidal plants; Carrageenans